Retraction of ‘Hydroethanolic extract of Sida rhombifolia L. ameliorates scopolamine-induced cognitive dysfunction in rats' (Journal of Applied Pharmaceutical Science, 2023)
The article titled ‘Hydroethanolic extract of Sida rhombifolia L. ameliorates scopolamine-induced cognitive dysfunction in rats’ which was published in the Journal of Applied Pharmaceutical Science, Volume: 11, Issue: 5, pp. 118-126, has been retracted from the Journal.The journal received a complaint that there is an error in figure 5 where some images have been repeated. After a thorough examination, we have identified instance of image duplication in the published article. The authors also confirmed that this was an unintentional error and one slide was duplicated in histopathology figure (figure 5).We suspect that the peer-review process may have been either compromised or not thorough, in this instance, which raise the concerns about the reliability of these results. Therefore, we retract this article from the literature according to the guidelines of the Committee on Publication Ethics (Wager et al., 2009; COPE, 2019).Read the related article: http://doi.org/10.7324/JAPS.2021.110516